SUPERVISED INTERNSHIP AND TRAINING: THE INFLUENCE OF THE REGENT TEACHER IN THE FIRST YEARS OF PROFESSIONAL LIFE OF GRADUATES IN PEDAGOGY - COSTA, Elisangela André da Silva (2022)
This article aims to analyze the formative contributions of the regent professors in the supervised curricular internship of the degree in Pedagogy for the teaching exercise of the graduating students in their first years of professional activity. Methodologically, the research is linked to the qualitative approach, the case study method and approximation with reality through unstructured questionnaires. Data analysis allowed us to verify that, despite being surrounded by movements of approximations and distances, the relationship established between interns and regents constitutes a significant formative experience for both. The knowledge built up during the internship and the actions developed in collaboration become references used repeatedly in the early years of exercising the profession, reaffirming the importance of supervised internships in the process of teachers’ identity construction.